I think that's what you mean
Yess what do you need help with
Answer:
-2
Step-by-step explanation:
![y = kx + n](https://tex.z-dn.net/?f=y%20%3D%20kx%20%2B%20n)
When you insert the given points you get
![3k + n = 4 \\](https://tex.z-dn.net/?f=3k%20%2B%20n%20%3D%204%20%5C%5C%20)
![7k + n = - 4 \\](https://tex.z-dn.net/?f=7k%20%2B%20n%20%3D%20%20-%204%20%5C%5C%20)
Than you multiply the first one by - 1 and sum it with the second to get rid of n
![4k = - 8 \\ k = - 2](https://tex.z-dn.net/?f=4k%20%3D%20%20-%208%20%5C%5C%20k%20%3D%20%20-%202)
Answer:
5b + 9
Step-by-step explanation:
You are essentially trying to simplify the expression given to you. To do so, combine terms with like terms:
4b + 9 + b
In this case, combine all terms with the same amount of variables, b.
(4b + b) + 9 = 5b + 9
5b + 9 is your answer.
~